Peran Guru Ngaji Dalam Meningkatkan Minat Pembiasaan Membaca Al-Qur’an Pada Santri RTQ Subulus Sholah di Kampung Siswo Bangun Seputih Banyak - Logaya, Siti; Aziz Q, Ikhwan; Arifin, M Zainal (Jurnal Keislaman, 2025)
This research is based on the decline in interest in reading the Qur'an that occurs in the nation's young generation among the factors causing it is negative parenting style, family interaction that is less supportive in creating a conducive home environment to stimulate children's interest in the habit of reading the Quran. This research aims to improve the habit of reading the Qur'an in children. The research approach uses a qualitative approach through a qualitative descriptive method The source of data for this research is the head of RTQ (raudhatul ta'limil qur'an), students and parents of RTQ subulus sholah. Data analysis technique with three main steps. namely data reduction, data display and data verification. The results of the study showed the development of Santri in the habit of reading the Quran.